Proteomic Analysis of Kiwifruit in Response to the Postharvest Pathogen, Botrytis cinerea - Liu, Jia; Sui, Yuan; Chen, Huizhen; Liu, Yiqing; Liu, Yongsheng (Frontiers in Plant Science, 2018)
Gray mold, caused by the fungus Botrytis cinerea, is the most significant postharvest disease of kiwifruit. In the present study, iTRAQ with LC-ESI-MS/MS was used to identify the kiwifruit proteins associated with the response to B. cinerea. A total of 2,487 proteins in kiwifruit were identified. Among them, 292 represented differentially accumulated proteins (DAPs), with 196 DAPs having increased, and 96 DAPs having decreased in accumulation in B. cinerea-inoculated vs. water-inoculated, control kiwifruits. DAPs were associated with penetration site reorganization, cell wall degradation, MAPK cascades, ROS signaling, and PR proteins. In order to examine the corresponding transcriptional levels of the DAPs, RT-qPCR was conducted on a subset of 9 DAPs. In addition, virus-induced gene silencing was used to examine the role of myosin 10 in kiwifruit, a gene modulating host penetration resistance to fungal infection, in response to B. cinerea infection. The present study provides new insight on the understanding of the interaction between kiwifruit and B. cinerea.